2000
DOI: 10.1001/archinte.160.14.2177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Walking Training on Weight Maintenance After a Very-Low-Energy Diet in Premenopausal Obese Women

Abstract: Inclusion of a walking program of moderate training regimen into a weight maintenance program improved maintenance of losses in weight and waist circumference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 37 publications
4
159
0
1
Order By: Relevance
“…The programs included yoga postures either alone or in combination with yoga breathing exercises and meditation. Walking was also found to favorably influence the body composition, as well as anthropometric and biochemical measures of persons of different age groups and of both sexes [2,911]. The present study results showed that a 15-day program of supervised yoga or of supervised walking had comparable beneficial effects in the variables assessed.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The programs included yoga postures either alone or in combination with yoga breathing exercises and meditation. Walking was also found to favorably influence the body composition, as well as anthropometric and biochemical measures of persons of different age groups and of both sexes [2,911]. The present study results showed that a 15-day program of supervised yoga or of supervised walking had comparable beneficial effects in the variables assessed.…”
Section: Discussionsupporting
confidence: 60%
“…Weight reduction can be achieved by several methods of varying degrees of usefulness [2], particularly high levels of physical activity [3,4] and a change in the attitude towards food choices [5,6]. Two methods compared in the present study are walking and yoga, due to their increasing popularity and relative safety when supervised [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, 18% of the placebo group and 38% of the lifestyle intervention group no longer had the syndrome after 3 years (Orchard et al 2005). Within a randomized study, Fogelholm et al (2000) showed a resolution of the MetS in 6 of 9 premenopausal obese women following 3 months of a very low-energy, dietary-induced weight reduction and weight-maintenance program focused on low-fat diet and cognitive eating control. However, all participants had a recurrent MetS diagnosis following long-term unsupervised follow-up.…”
Section: Mets: Prevalence and Resolutionmentioning
confidence: 96%
“…Accordingly, reducing psychological barriers and increasing motivation and self-efficacy for lifestyle modifications have been indicated as relevant strategies for longterm interventions (Deci and Ryan 1985;Delahanty et al 2006). Some researchers (e.g., Miller 1999) have been critical of the typical treatment modalities proposed for the MetS, where behaviour modification is used to encourage restrictive dieting in conjunction with increased exercise, primarily as a means to attain weight loss (Fogelholm et al 2000;Foreyt 2005). By contrast, the ''Health at Every Size'' (HAES) paradigm for obesity treatment, proposes that improved health is a consequence of lifestyle changes that are independent of body mass (Miller and Jacob 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This sample size is, however, considerably larger than many trials of WLM interventions. [148][149][150][151][152] In a systematic review of WLM following at least 1 month of intervention and then 1 year of no intervention, the sample sizes of the 12 included studies 152 (with 22 intervention groups) [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169] ranged from 44 170 to 241, 171-173 with only three studies having a larger sample size than the present study. There are no studies of MI for WLM; however, in a review of studies using MI as an intervention for weight loss, only one-third of the 12 included studies had a larger sample size than the current study and the range was 22-599.…”
Section: Interpretation and Comparison With Previous Studiesmentioning
confidence: 99%